(untitled) (Colombia Medica, 2022)
Successive measurements of global disease burden have documented that lower respiratory tract infections, including pneumonia, are among the top 10 causes of disability-adjusted life-years, and in 2019, pneumonia was the fourth cause of mortality for all ages. In Colombia, acute respiratory infections are the leading cause of mortality within the group of infectious diseases, 52.3% of the total reported between 2005 and 2019. Notably, the COVID-19 epidemic increased the impact of respiratory tract infections on the global disease burden, with estimates of 18 million excess deaths from January 2020 to December 2021 worldwide. The assessment of an adult with pneumonia or suspected pneumonia demands the identification of the likelihood of death and hospitalization. Several scales have been constructed to estimate this probability to improve the predictive capacity of clinical evaluation. Among these scales, the CRB-65 and the CURB-65 standout, being the first recommended for use with clinical criteria and the second when laboratory data such as urea nitrogen are available. Additionally, for an individual with sepsis, there have been developed to predict mortality, such as SOFA (Sequential Organ Failure Assessment) and, more recently, the qSOFA(quick SOFA), which has an accurate prediction of mortality in this population. Hincapié C et al. assessed the CURB-65, CRB-65 and SOFA scales to predict mortality and admission to the intensive care unit in adults with pneumonia in three cohorts of patients admitted in three medium- and high-complexity hospitals in the city of Medellin-Colombia. The study included 1110 patients with suspected pneumonia identified in the emergency department and followed up until discharge and death. The authors found that the highest discrimination capacity, measured by the ROC curve, for the outcome hospitalization in an intensive care unit was 0.61, 0.58, and 0.59 for the CURB-65, CRB-65, and SOFA, respectively. About mortality, the ROC found was 0.66, 0.63, and 0.63 for CURB-65, CRB65, and SOFA, respectively. The calibration was appropriate, that is, the ability to predict mortality and admission to the intensive care unit e for the three scales. Some readers have expressed their disagreement with the possible limited use of the scales, particularly the CURB-65 and the CRB-65, in the evaluation of an adult patient with pneumonia expressed by the authors.